The Marketing Implication in Attracting Tourists to Oxian Alexandria in Termez - Sobirjonovna, Sitora Shaydullaeva; Azamat, Jozilov (European Journal of Life Safety and Stability (2660-9630), 2021)
The purpose of this study is to study the history of the lost historical city, Oxian Alexandria, found in the Surkhandarya region, and to protect this historic site and attract tourists. After the independence of Uzbekistan, more attention was paid to the cultural and historical heritage of our ancestors, historical monuments were taken under state control. During the years of independence Bukhara, Samarkand, Termez, Khiva, Tashkent. Kokand. Monuments built in cities such as Shakhrisabz with the high talent of our great ancestors have found their true value, their repair and restoration has become one of the priorities of state policy. Preservation of our past, respect for historical monuments, relics, as well as the great past of our people, the social life in which they live and the future are directly related. These features are the national values of our nation and people, which have long been ingrained in their blood. Therefore, the current problem is to preserve these historical monuments as much as possible and to thoroughly study the history of some historical places that were hitherto unknown to the public.